2018
DOI: 10.1186/s13018-018-0879-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of AC dislocation by reconstructing CC and AC ligaments with allogenic tendons compared with hook plates

Abstract: BackgroundThe purpose of this study was to compare outcomes between allograft reconstruction and hook plate fixation for acute dislocation of the acromioclavicular joint with a minimum 2-year follow-up.MethodsA retrospective comparative study of patients treated for acute acromioclavicular joint dislocation from February 2010 to December 2014 in our hospital, consisting of 16 patients who were followed-up, was performed.Eight patients were treated for acute AC dislocation and underwent surgical reconstruction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…Recently, some authors have suggested CC ligament reconstruction by using tendon grafting [23]. However, in another study, 47% reduction loss and 20% complications were seen after CC ligament reconstruction with an autologous tendon graft, which adversely affected the results [11].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some authors have suggested CC ligament reconstruction by using tendon grafting [23]. However, in another study, 47% reduction loss and 20% complications were seen after CC ligament reconstruction with an autologous tendon graft, which adversely affected the results [11].…”
Section: Discussionmentioning
confidence: 99%
“…A pad was placed beneath the scapula. A saber cut incision 61 , 72 , 78 was made in line from the coracoid process to the medial AC joint.…”
Section: Methodsmentioning
confidence: 99%
“…This advantage was shown by Wang et al in their clinical comparison of suspensory device fixation with additional tendon allograft compared to hook plating. 46 Additionally, Millett et al 47 described the advantage of suspensory device fixation in relation to its arthroscopically assisted approach, which allows for the detection of concomitant glenohumeral pathologies associated with acute and chronic acromioclavicular joint injuries. 24 Clinical short-term results after suspensory device fixation showed excellent postoperative outcome scores (mean ASES score of 93.8 points) and no further revision surgery, however, complications occurred in 23%.…”
Section: Suspensory Devicesmentioning
confidence: 99%